Testing the link between genome size and growth rate in maize - Maud I. Tenaillon; Domenica Manicacci; Stéphane D. Nicolas; Francois Tardieu; Claude Welcker (PeerJ, 2016)
Little is known about the factors driving within species Genome Size (GS) variation. GS may be shaped indirectly by natural selection on development and adaptative traits. Because GS variation is particularly pronounced in maize, we have sampled 83 maize inbred lines from three well described genetic groups adapted to contrasted climate conditions: inbreds of tropical origin, Flint inbreds grown in temperate climates, and Dent inbreds distributed in the Corn Belt. As a proxy for growth rate, we measured the Leaf Elongation Rate maximum during nighttime (LERmax) as well as GS in all inbred lines. In addition we combined available and new nucleotide polymorphism data at 29,090 sites to characterize the genetic structure of our panel. We found significant variation for both LERmax and GS among groups defined by our genetic structuring. Tropicals displayed larger GS than Flints while Dents exhibited intermediate values. LERmax followed the opposite trend with greater growth rate in Flints than in Tropicals. In other words, LERmax and GS exhibited a significantly negative correlation (r = − 0.27). However, this correlation was driven by among-group variation rather than within-group variation—it was no longer significant after controlling for structure and kinship among inbreds. Our results indicate that selection on GS may have accompanied ancient maize diffusion from its center of origin, with large DNA content excluded from temperate areas. Whether GS has been targeted by more intense selection during modern breeding within groups remains an open question.